Refusal Strategies in the Movie The Walking Dead - Dede Rama Rifandi; Wahyu Kamil; Wiyasukti Ningksih (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2019)
This research discussed refusal strategies used by the characters in the movie The Walking Dead in season 9 featuring 16 episodes. This research aimed to find out type of refusal strategies and the mostly used by the characters in the movie. This research focused on Beebe, Takahashi and Uliss-Weltz’s theory about direct and indirect refusal. Then, the data were analyzed by using qualitative descriptive method. To get the data, it used subtitle itself on the movie by watching all of episodes to find out valid data. The research results show that there are 35 data. There were 18 direct refusal, 13 indirect refusal and four data that used two strategies in one conversation. Therefore, the mostly used is direct refusal, 18 times. Direct refusal used non-performative statement and negative willingness while indirect refusal used as giving reason, explanation, attempt to dissuade interlocutor, statement of regret, avoidance (verbal and non-verbal), unspecific reply, and adjuncts to refusal that is appreciation.